2018
DOI: 10.1101/gad.316802.118
|View full text |Cite|
|
Sign up to set email alerts
|

Single-nucleus transcriptomic survey of cell diversity and functional maturation in postnatal mammalian hearts

Abstract: A fundamental challenge in understanding cardiac biology and disease is that the remarkable heterogeneity in cell type composition and functional states have not been well characterized at single-cell resolution in maturing and diseased mammalian hearts. Massively parallel single-nucleus RNA sequencing (snRNA-seq) has emerged as a powerful tool to address these questions by interrogating the transcriptome of tens of thousands of nuclei isolated from fresh or frozen tissues. snRNA-seq overcomes the technical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 56 publications
8
87
0
Order By: Relevance
“…This disparity might be due to different isolation protocols, on the one hand, and the fact that we used whole hearts instead of isolated ventricles, on the other hand. However, more recent findings, also based on single-nucleus sequencing [5], are in accordance with our data, so that we further assume that this kind of holistic approach may yield more robust results than approaches relying on single-marker genes. Moreover, we not only observed various immune cells but also identified cells of neuronal origin (7.4%) and cardiac glial cells (0.2%) representing the innervated system of the heart and confirming the comprehensiveness of our data.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This disparity might be due to different isolation protocols, on the one hand, and the fact that we used whole hearts instead of isolated ventricles, on the other hand. However, more recent findings, also based on single-nucleus sequencing [5], are in accordance with our data, so that we further assume that this kind of holistic approach may yield more robust results than approaches relying on single-marker genes. Moreover, we not only observed various immune cells but also identified cells of neuronal origin (7.4%) and cardiac glial cells (0.2%) representing the innervated system of the heart and confirming the comprehensiveness of our data.…”
Section: Resultssupporting
confidence: 92%
“…Whereas research efforts aim to avoid these issues by relying on embryonic and neonatal murine hearts or focusing on non-myocyte populations in adult mouse hearts, we desisted from single-cell Ribonucleic acid sequencing (RNA-seq) and instead conducted single-nucleus RNA-seq (snRNA-seq), which has been shown to present similar transcriptomic results [3]. Currently, existing studies on adult mammalian hearts concentrate only on selected substructures such as the ventricle [4] or the conduction system [5]. To our knowledge, we present the first snRNA-seq analysis of an entire adult mammalian heart.…”
Section: Introductionmentioning
confidence: 99%
“…A single-cell RNA-seq analysis identified two major fibroblast populations in adult mouse ventricles; however, the distribution of expression of an epicardium marker amongst the cells indicated that these clusters do not reflect the two developmental origins [67•]. Similarly, a single-nucleus transcriptomic approach of early postnatal heart tissue identified two fibroblast populations that were actually only subtly different and both expressed high levels of specific ECM genes (periostin, fibrillin 1 and collagen 5a1) [68]. Further exploration into the overlap, sub-clustering and differing functions of these populations is warranted.…”
Section: Fibroblast Heterogeneity In Development Homeostasis and Fibmentioning
confidence: 99%
“…However, this approach is technically challenging, low throughput, and time intensive, which may in turn lead to significant transcriptomic changes during isolation. In lieu of whole cell scRNA-seq, others have utilized single nuclear RNA-seq (snRNA-seq), which overcomes the challenges of isolating large CMs [14][15][16] . While this approach can broadly capture cellular heterogeneity, snRNA-seq inherently detects fewer molecules and may skew gene expression towards transcripts predominantly localized in the nucleus (e.g.…”
mentioning
confidence: 99%